Optimal Control of the Position of Moisture Transfer Sources in Porous Media - Tymoshenko, Andrii; Klyushin, Dmitriy; Lyashko, Sergey; Lyashko, Natalia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The paper proposes an approach for finding the optimal position of sources of known power for the quasi-linear Richards equation in a rectangular area. The Kirchhoff transformation is applied with the introduced scaling of coordinates and powers of submerged sources, which allows formulating a dimensionless problem. The task of this study is to find the position of submerged sources - such that the distribution of moisture at the final moment of time is close to the given values or the given target function.